APPLICATION OF METHODS FOR DEVELOPING PROFESSIONAL COMPETENCE IN FUTURE ELECTRICIANS AT AGRICULTURAL COLLEGES - Yarosh, Lyubov (Professional Pedagogics, 2023)
Relevance: The relevance is determined by the reform of the content, methods, forms, and technologies of professional higher education, which is carried out based on a competence-based approach and identifies the need for a comprehensive application of teaching methods in the process of developing professional competence in future electricians at agricultural colleges.Objective: To identify and characterize a set of methods for developing the professional competence of future electricians at agricultural colleges.Methods: Theoretical analysis of sources - to determine the state of development of methods for developing the professional competence of future electricians at agricultural colleges; systematization and summarization of the results of theoretical understanding of scientific works, best educational practices, and personal experience - to identify and justify the methodological features of developing professional competence in future electricians at agricultural colleges and determine the most conducive methods for this purpose.Results: Methodological peculiarities and mechanisms for developing professional competence in future electricians in educational practice have been identified; successful examples of using individual methods in the study of electrotechnical disciplines are provided; the most optimal methods for developing professional competence in future electricians at agricultural colleges have been determined.Conclusions: A set of methods for developing professional competence in future electricians at agricultural colleges has been identified (explanatory-illustrative, reproductive, problem-based, partial-search, heuristic, research methods); it is shown that their combination in the professional training of future electricians at agricultural colleges significantly improves the success of assimilating general educational and professional knowledge and developing practical skills and abilities of learners.
Keywords: explanatory and illustrative methods; reproductive methods; problem presentation methods; partial search or heuristic methods; research methods